New insights into radioresistance in breast cancer identify a dual function of miR‐122 as a tumor suppressor and oncomiR - Isidro X. Perez‐Añorve; Claudia H. Gonzalez‐De la Rosa; Ernesto Soto‐Reyes; Fredy O. Beltran‐Anaya; Oscar Del Moral‐Hernandez; Marisol Salgado‐Albarran; Oscar Angeles‐Zaragoza; Juan A. Gonzalez‐Barrios; Daniel A. Landero‐Huerta; Margarita Chavez‐Saldaña; Alejandro Garcia‐Carranca; Nicolas Villegas‐Sepulveda; et al. (Molecular Oncology, 2019)
Radioresistance of tumor cells gives rise to local recurrence and disease progression in many patients. MicroRNAs (miRNAs) are master regulators of gene expression that control oncogenic pathways to modulate the radiotherapy response of cells. In the present study, differential expression profiling assays identified 16 deregulated miRNAs in acquired radioresistant breast cancer cells, of which miR‐122 was observed to be up‐regulated. Functional analysis revealed that miR‐122 has a role as a tumor suppressor in parental cells by decreasing survival and promoting radiosensitivity. However, in radioresistant cells, miR‐122 functions as an oncomiR by promoting survival. The transcriptomic landscape resulting from knockdown of miR‐122 in radioresistant cells showed modulation of the ZNF611, ZNF304, RIPK1, HRAS, DUSP8 and TNFRSF21 genes. Moreover, miR‐122 and the set of affected genes were prognostic factors in breast cancer patients treated with radiotherapy. Our data indicate that up‐regulation of miR‐122 promotes cell survival in acquired radioresistant breast cancer and also suggest that miR‐122 differentially controls the response to radiotherapy by a dual function as a tumor suppressor an and oncomiR dependent on cell phenotype.